Al-Falah dalam Konsepsi Al-Qur’an - Hasibuan, Heny Liya (IAIN Takengon, 2021)
This article aims to know the concept of al-falah in the Qur'an. Al-Falah is defined as success. Success in the world is for example a form of wealth in business, the result of work to make a living that is financially profitable, while immaterial luck such as the purity of the soul, the spiritual side that will guide goodness. And the hereafter is the forgiveness of Your Lord, and His reward is good, and he is the All-mighty, the Allwise. Success (al-falāḥ) is only seen when the meaning of success (al-falāḥ) deals with those who obtain it (al-muflihūn), and when dealing with business or good deeds to obtain success (al-falāḥ). Similarly, success (al-falāḥ) is also seen when faced with those who fail to obtain success (al-falāḥ) as wrongdoers, and so on. Success (al-falāḥ) is necessary both for life in this world and in the hereafter